The effects of organizational, work and individual factors on teachers' work-life balance - Nurul Atikah, Ahmad (2019)
This study was conducted to identify the effects of organizational factor (public vs. private school, secondary vs. primary school, and urban vs. rural school), work factor (gender and marital) and individual factors (job grade and job position) on teachers’ work-life balance. A total of 258 teachers from 11 schools in Kedah have participated in this study. The data was collected by using self-administered questionnaires and SPSS was used to analyses the data and test hypothesis. The result shows that types of schools in term of primary and secondary school, and gender have a significant effect on the work-life balance of teachers. However, the other variables such as types of school (public, private, urban and rural), job grade, job position, and marital status do not have a significant effect on the work-life balance of teachers. Based on the findings, it is suggested that any work-life balance program provided by management of education sector should focus on the work-life balance of secondary and female teachers.